Patterns and genomic correlates of PD-L1 expression in patients with biliary tract cancers - Kabir Mody; Jason S. Starr; Michelle Saul; Kelsey Poorman; Benjamin A. Weinberg; Mohamed E. Salem; Ari M. Vanderwalde; Anthony F. Shields (2019)
Background: Patients with biliary tract cancer (BTC) have a dismal prognosis and limited treatment options. Given the potential for immunotherapy in patients with BTC, we studied the expression of programmed death ligand-1 (PD-L1)/programmed death-1 (PD-1) and evaluated for associated genetic alterations in patients with BTC. Methods: By immunohistochemistry (IHC), PD-L1 (SP142 antibody; ≥2+ and/or ≥5% staining on tumor cells considered positive) and PD-1 [NAT105 antibody; ≥1+ staining of tumor infiltrating lymphocytes (TILs) considered positive] expression was studied and next-generation sequencing (NGS) was performed using Caris Life Sciences’ sequencing panel of 592 genes. A total of 652 patients with BTC were included in this study: 77 extrahepatic cholangiocarcinoma (ECC), 203 gallbladder cancer (GBC), and 372 intrahepatic cholangiocarcinoma (ICC). Results: Of the 652 tumors 8.6% were PD-L1 positive with the following distribution: GBC 12.3% (25/203), ICC 7.3% (27/372), and ECC 5.2% (4/77). There was a statistically significant increase in BRAF, BRCA2, RNF43, and TP53 mutations in PD-L1 positive group as compared to PD-L1 negative. Among other biomarkers tested, TOP2A, tumor mutational burden (TMB) high (≥17 mutations per megabase) (10.7%), and microsatellite instability high (MSI-H) (7.1%) were increased in PD-L1 positive tumors versus PD-L1 negative tumors. Conclusions: PD-L1 expression was noted in a small percentage (8.6%) of patients with BTC. This finding suggests potential benefit of immunotherapy in this subset of patients. Furthermore, there was a statistically significant association between PD-L1 expression and certain genomic alterations (BRAF, BRCA2, RNF43, TP53) and biomarkers (TOP2A, TMB high, MSI-H), which might direct the use of rational combination strategies and clinical trial development.